Performance of Using Porous Floating Cylindrical Breakwater with Different Porosities as a Wave Energy Dissipater in Experimental Study - El Saie, Y. M. (Advances in Social Sciences Research Journal, 2019)
Floating breakwaters are commonly used to protect shorelines, marine structures and harbors from wave attacks. Through the physical model test method, the wave energy dissipation performance by using porous floating cylindrical breakwater under regular waves. This research content in this paper for a horizontal cylindrical pipe with different diameters and with different percentage of porosity working as a single pipe or as a group. Which contains five different models with diameters (2 inch, 3 inch, 4 inch, (3&4 inch together) and (2, 3 & 4 inch together) by choosing different percentage of porosities (15, 30 & 50%) to achieve maximum energy dissipation with minimum transmitted energy. The experiments were carried out in a recirculating open channel flume located at the Hydraulics Engineering Laboratory, Higher Institute of Engineering in El Shorouk City.